IMPLEMENTASI UNDANG-UNDANG NOMOR 22 TAHUN 2022 TENTANG PEMASYARAKATAN TERKAIT PEMBINAAN KEPRIBADIAN TERHADAP RESIDIVIS NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS II B SINGARAJA - I Kadek Subadra; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Jurnal Ilmu Hukum Sui Generis, 2023)
This study aims to provide knowledge related to the implementation of Law Number 22 of 2022 concerning Correctional Services related to personality development for narcotics recidivists serving sentences in prisons, as well as to find out the factors that hinder the implementation of personality coaching in the Class II B Singaraja Correctional Institution.This research also aims to provide knowledge about narcotics addicts who should receive facilities in the form of medical and social rehabilitation. The type of research used in this research is empirical research with descriptive research characteristics. This research was conducted at the Class II B Singaraja Correctional Institution. The data collection technique was carried out by Non Probability Sampling and processed by qualitative descriptive techniques. The results of the study show that regarding the implementation of Law Number 22 Concerning Corrections regarding the personality development of narcotics recidivists in the Class II B Singaraja Correctional Institution has not been fully implemented. This is because there are factors that hinder the implementation of personality development for narcotics recidivists in Class II B Singaraja Correctional Institution. The inhibiting factors are the number of convicts who exceed capacity, the lack of budget in implementing personality development, correctional officers who have not fully mastered the skills, and the lack of facilities and infrastructure.